Tensions in the East China Sea : time to contain naval stand-offs - Koh, Collin Swee Lean (2013)
Recently, a Chinese frigate reportedly locked its radar onto a Japanese destroyer in the East China Sea, escalating Sino-Japanese tensions over the Senkaku/Diaoyu Islands disputes. This warrants a serious look at operational naval arms control for all stakeholders.